Identification of a Plasma MicroRNA Profile Associated With Venous Thrombosis. Issue 5 (May 2020) - Rodriguez-Rius, Alba; Lopez, Sonia; Martinez-Perez, Angel; Souto, Juan Carlos; Soria, Jose Manuel
Abstract : Objective: Venous thrombosis (VT) is a complex condition with a highly heritable genetic component that predisposes one to its development. Certain microRNAs (miRNAs) might be used as biomarkers of VT, but few studies have examined miRNA expression in this respect. The aim of the present work was to identify a plasma miRNA profile associated with VT. Approach and Results: miRNAs were analyzed by quantitative polymerase chain reaction in plasma samples from members of the GAIT-2 (Genetic Analysis of Idiopathic Thrombophilia 2) population (n=935). A discovery phase involving the screening of 752 miRNAs from a subset of 104 GAIT-2 subjects was followed by an internal validation phase in which the selected miRNAs were quantified in the whole GAIT-2 population. In the discovery phase, 16 miRNAs were selected, including 9 associated with VT and 7 that correlated with an intermediate phenotype of VT. In the next phase, 4 miRNAs were validated as differentially expressed (false discovery rate, <0.1) in VT: hsa-miR-126-3p, hsa-miR-885-5p, hsa-miR-194-5p, and hsa-miR-192-5p. The 4 miRNAs each returned a significant ( P <0.05) odds ratio for VT (range of 1.3–1.8). A risk model including the 4 miRNAs, age, and sex returned an area under the receiver operating characteristic curve of 0.77. Moreover, all 4 miRNAs showed significant correlations with intermediate phenotypes of VT (eg, protein S and factor VII). The targets of the miRNAs in the blood coagulation pathway and their interactions are also discussed. Conclusions: The present results suggest a 4-miRNA plasma profile associated with VT is of potential use in predicting the risk of this condition. Abstract : Supplemental Digital Content is available in the text.